Effect Of Pilates Exercises, Yogic Practices and Combined Pilates Exercises and Yogic Practices on Selected Physical Fitness Variables Among College Female Students - Aruna, K.; Parthiban, I. John (Journal of Neonatal Surgery, 2025)
Background: The present study was designed to find out the effect of Pilates exercises, yogic practices and combined Pilates exercises and yogic practices on selected physical fitness variables among college female students. Methods: For this purpose, sixty (N=60) college female students studying various affiliated colleges to Thiruvalluvar University, Vellore, Tamilnadu India were selected randomly as subjects. The age of the subjects was ranged between 18-21 years. The subjects were assigned at random into four groups of fifteen each (n=15) namely, Pilates exercises, yogic practices, combined Pilates exercises and yogic practices and control group. Group-I underwent Pilates Exercises, Group-II underwent yogic practices, Group-III underwent combined Pilates exercises and yogic practices and Group-IV acted as control. The duration of the training period for all the three experimental groups was restricted to twelve weeks and the number of sessions per week was confined to three in a week. For combined Pilates exercises and yogic practices, the training period was restricted to alternative weeks for twelve weeks. Among various physical fitness variables Agility and Flexibility were selected as dependent variable and agility assessed by 4x10 meters shuttle run test and flexibility was measured through sit & reach test. All the subjects were tested prior to and immediately after the training for the entire selected variable. Results: The data obtained from the experimental groups before and after the experimental period were statistically analyzed with Analysis of covariance (ANCOVA). Whenever the ‘F’ ratio for adjusted posttest means was found to be significant, the Scheffe’s Post hoc test was applied to determine the paired mean differences. The level of confidence was fixed at 0.05 level for all the cases. Conclusions: The results of the study showed that there was a significant difference among all the groups. Further the results of the study showed that combined Pilate’s exercises and yogic practices group was found to be better than the Pilate’s exercises group and yogic practices group in agility and flexibility